Study on the Phenomenon of Flood Characteristic in DKI Jakarta - Koto, J; Negara, Ridho Bela; Tasri, Adek; Kamil, Insannul (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Since Dutch era, flood has become serious issues faced by DKI Jakarta. Study on prevention flood program has also been conducted since Dutch era. In rainy season, common flooding is caused by several factors as follows: lowland areas in the northern part of Jakarta below sea level, urbanization rate, irregular population density, slum neighborhood where scattered rubbish where quickly provoke the flood to stagnate and increase rather than receding. This flood is mainly caused by not only above factors but also land subsidence an average of 5-10 cm every year. This paper discusses on flood characteristics in DKI Jakarta. In the study, firstly history of flood was discussed started in Dutch era until after independence. It was founded that floods occur in continuous heavy rains like in January and February. There is a combination of floods caused by rain in the upstream and downstream. Previously heavy rains can cause flooding in subsequent heavy rains.